(untitled) (World Economics and Finance Bulletin, 2022)
Sources of income diversify and increasing the state public revenues is one of the most important challenges facing the rentieral economies that depend on the export of raw materials such as oil. The returns are exposed to fluctuations and fluctuations in global markets. The emphasis on sources of income must include all available and possible sources, especially taxes and their revenues, including direct and indirect taxes. The most important characteristic of rentieral countries is the absence of transparency and accountability and the absence of tax returns. Also, these countries will be more vulnerable to economic risks, especially oil, due to price fluctuations, which will lead to structural imbalances and turmoil in conditions externally and internally and the emergence of economic and financial crises. It is a result of their dependence on a single source of income. Therefore, this is reflected on the state’s macroeconomic indicators in the event of a decline in prices